Influence of Terpenic Oil on Flotation Behavior of Sphalerite and Implication for the Selective Separation - Bo Yang; Xian Xie; Xiong Tong; Lingyun Huang (Adsorption Science & Technology)
Terpenic oil (TO) is commonly used as a flotation frother for the selective separation of sulfide minerals. As a frother, most reports have mainly focused on its effect on froth stability and froth entrainment, whereas its influence on the floatability of sulfide minerals has received little attention. In this work, the influence of TO on the flotation behavior of sphalerite was investigated by using microflotation tests, contact angle and zeta potential measurements, and FT-IR and SEM-EDS analyses. Microflotation tests conducted in a modified Hallimond tube indicated that compared with the collector potassium butyl xanthate (KBX), the flotation recovery of sphalerite was significantly increased when TO was added to the pulp, but the recovery of Cu-activated sphalerite with the addition of TO was lower than that with the addition of KBX. Contact angle measurements demonstrated that the contact angle of sphalerite was distinctly increased by the addition of TO, but the contact angle of sphalerite treated with TO was lower than that treated with KBX after Cu activation. Zeta potential measurements demonstrated that the zeta potential of sphalerite particles was slightly decreased when treated with TO, and the isoelectric point (IEP) was decreased from 3.3 to 3.1 due to the interaction of TO with sphalerite particles. FT-IR and SEM-EDS confirmed that TO could be adsorbed on the sphalerite surface on the formation of the oil film due to its low solubility, thereby increasing the surface hydrophobicity of the sphalerite. In addition, the TO absorbed on the surface acts as a bridging role and promotes the hydrophobic agglomeration of sphalerite particles. These results suggest that except for froth entrainment, the influence of TO on the flotation behavior of sphalerite may be another reason for the misreporting of sphalerite in concentrates.